Coding‐Feeding Metasurface for Diffusion and Dual‐Band Emission. Issue 8 (31st March 2022) - Huang, Guo Shuai; Li, Si Jia; Li, Zhuo Yue; Liu, Xiao Bin; Ji Di, Liao Ri; Cao, Xiang Yu
Abstract: As 2D metamaterials, metasurfaces are well known due to the distinctive manipulation of the amplitude, phase, polarization, and propagation for electromagnetic (EM) waves. However, the existing metasurfaces are mainly designed to control the incident waves. Herein, a coding‐feeding metasurface (CFMS) with two functions of dual‐band emission and diffusion for incidences simultaneously is proposed. The zigzag emission patch and two arc‐split triangle patches for polarization conversion are nested together on a shared aperture of a unit cell for CFMS. The genetic optimization algorithm is introduced for diffusion. A prototype is fabricated and measured to validate the proposed CFMS with dual‐function. The experimental results agree well with the simulated data, which verify the diffusion and emission for CFMS. The CFMS with the lightweight, compact, and low profile has the potential applications in imaging, detection, and wireless communication systems for stealth aircraft. Abstract : A coding‐feeding metasurface is proposed with two functions of the diffusion for incidences and the dual‐band emission. The genetic optimization algorithm is used to optimize the distribution of coding subarrays for scattering diffusion. The coding‐feeding metasurface paves a way to practical applications such as detection system and wireless communication for the stealth aircraft.